Proactive champions: How personal and organizational resources enable proactive personalities to become idea champions - De Clercq, D.; Pereira, R. (Journal of Social Psychology, 2023)
In investigating the relationship between employees’ proactive personality and idea championing, this study addresses how this relationship might be augmented when employees can draw from pertinent personal resources (persuasion self-efficacy and job enthusiasm) and organizational resources (social interaction and organizational support for change). Two-wave survey data, collected among employees in a banking organization, show that employees’ proactive personalities increase the likelihood that they mobilize support for innovative ideas, especially if they (1) feel confident that they can defend these ideas successfully, (2) experience their jobs as sources of personal fulfillment, (3) maintain informal relationships with peers, and (4) believe their organizations embrace change. For managers, these findings indicate that employees will leverage their positive energy, derived from their desire for initiative taking, into enhanced change-oriented championing activities if they also can draw from pertinent resources that enhance their ability or motivation to engage in those leveraging efforts.